Concrete double-K fracture toughness and fracture energy influenced by porosity and pore size - Guohui Zhang; Dejin Gu; Yanshuang Gu; Mingyang Zhou; Bo Zhao; Mingming Wang (Scientific Reports)
Abstract The diameter and quantity of internal pores in concrete significantly influence its mechanical properties. While existing studies predominantly focus on the influence of pore quantity, this study utilizes pre-fabricated pores made from polystyrene particles (EPS) to investigate the effects of different pore diameter and porosity on the fracture mechanical properties of concrete. The results indicate that the incorporation of EPS degrades the fracture mechanical properties of concrete. The initiation load, peak load, initiation fracture toughness, instability fracture toughness, and fracture energy of concrete all decrease with increasing porosity. At constant porosity, the initiation load and initiation fracture toughness of concrete with a hole diameter of 0.3 to 0.6 mm decreased the most, with maximum reductions of 48.98% and 49.30%, respectively. The peak load, instability fracture toughness and fracture energy of concrete with a hole diameter of 3 to 5 mm decreased the most, with maximum reductions of 26.88%,38.46%,24.02%, respectively. In comparison to porosity, pore size has a more significant impact on the initiation fracture toughness of concrete. The influence of porosity on the instability fracture toughness and fracture energy of concrete is greater than that of pore size.